OP0126 Evaluating low disease activity definitions in psoriatic arthritis using ultrasound. (12th June 2018) - Bosch, P.; Husic, R.; Ficjan, A.; Gretler, J.; Lackner, A.; Graninger, W.; Duftner, C.; Hermann, J.; Dejaco, C.
Abstract : Background: Cut offs for low disease activity (LDA) using psoriatic arthritis (PsA) specific composite scores have recently been proposed. 1–3 Whether these definitions adequately reflect the absence of inflammation is unknown. Objectives: To evaluate these definitions against a low level of activity according to ultrasound examination. Methods: We performed a prospective study on 83 PsA patients undergoing clinical and ultrasound examinations at two study visits scheduled 6 months apart. LDA was assessed using the Disease Activity index for Psoriatic Arthritis (DAPSA≤14), the Psoriatic ArthritiS Disease Activity Score (PASDAS ≤3.2), the Composite Psoriatic Disease Activity Index (CPDAI≤4), the Disease Activity Score 28 CRP (DAS28-CRP≤2.8) and the Minimal Disease Activity criteria (MDA). Ultrasound (US) evaluation was performed at 68 joints (evaluating synovia, peritendinous tissue, tendons and bony changes) and 14 entheses. Minimal ultrasound disease activity (MUDA) was defined as a Power Doppler (PD) score ≤1, respectively at joints, peritendinous tissue, tendons and entheses. Results: LDA was present in 33.7%–65.0% of patients at baseline and in 44.3%–80.6% at follow-up examination, depending on the criteria used. MUDA was observed in 16.9% at baseline and in 30% at follow-up. At baseline only the DAPSA-LDA definition was useful to identify MUDA patients (78.6% of patients identified correctly), whereas at follow up >80% of MUDA patients were correctly classified as LDA according to DAPSA, PASDAS, CPDAI and DAS28-CRP. Only DAPSA (Sensitivity (S)=88.2%, Specificity (Sp)=40.5, p=0.033), PASDAS (S=88.2%, Sp=55.0%, p=0.002) and the MDA criteria (S=71.4%, Sp=67.3%, p=0.003) were able to discriminate patients with and without MUDA at follow-up. A global ultrasound inflammation subscore for joints and entheses (GUIS-j/e), containing the above mentioned US variables, was significantly higher in patients with active disease versus patients in LDA according to DAPSA (p=0.002) and PASDAS (p=0.013) at baseline and DAPSA (p=0.007), PASDAS (p=0.001), CPDAI (p=0.021) and the MDA criteria (p<0.001) at follow up. Conclusions: Of all tested LDA definitions, DAPSA was overall the most efficacious in differentiating between high and low ultrasound scores and better identified patients with MUDA as compared to the other tested scores. References: [1] Coates LC, Fransen J, Helliwell PS. Defining minimal disease activity in psoriatic arthritis: A proposed objective target for treatment. Annals of the Rheumatic Diseases69(1):48–53. [2] Helliwell PS, FitzGerald O, Fransen J. Composite disease activity and responder indices for psoriatic arthritis: A report from the GRAPPA 2013 meeting on development of cutoffs for both disease activity states and response. The Journal of Rheumatology2014;41(6):1212–7. [3] Schoels MM, Aletaha D, Alasti F, Smolen JS. Disease activity in Psoriatic Arthritis (PsA): Defining remission and treatment success using the DAPSA score. Ann Rheum Dis2016;75(5):811–8. Disclosure of Interest: None declared